2018
DOI: 10.1159/000497236
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Esophageal Eosinophilia in Patients with Inflammatory Bowel Disease

Abstract: Background: The overlap between eosinophilic esophagitis (EoE) and inflammatory bowel disease (IBD) has not been extensively examined. We aimed to assess the prevalence of esophageal eosinophilia in patients with IBD. Methods: We conducted a retrospective cohort study using diagnostic codes to identify adults with EoE and IBD between 2008 and 2016 at a tertiary care center. Electronic medical records were reviewed to extract clinical, endoscopic, and treatment data. Patients with esophageal eosinophilia and IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
1
18
2
1
Order By: Relevance
“…However, 6% of the total patients had biopsies consistent with eosinophilic esophagitis. A previous population study demonstrated an increased prevalence of eosinophilic esophagitis in patients with IBD [22]. Gastritis was the most common upper gastrointestinal tract pathology finding, being present in nearly three-fourths of patients.…”
Section: Discussionmentioning
confidence: 86%
“…However, 6% of the total patients had biopsies consistent with eosinophilic esophagitis. A previous population study demonstrated an increased prevalence of eosinophilic esophagitis in patients with IBD [22]. Gastritis was the most common upper gastrointestinal tract pathology finding, being present in nearly three-fourths of patients.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, there were no significant differences in the endoscopic or histological findings based on the presence or absence of autoimmune disease. Fan et al reported no substantial clinical, endoscopic, or histologic differences between EoE patients with and without inflammatory bowel disease (IBD) ( 33 ). In several case reports of coexisting Crohn's disease and EoE ( 34 - 36 ), EoE developed after the induction of remission of Crohn's disease, suggesting that these diseases might be reciprocal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inflammation in the esophagus is unspecific [ 123 , 124 ] and rather has a lymphocytic than an eosinophilic pattern [ 125 , 126 ]. Although a recent publication showed a fivefold increased risk of EE in IBD [ 127 ], it is possible that most of these patients had rather an EoE than an isolated EE. Large epidemiologic data support a positive association between IBD and EoE with a up to fivefold increased risk of EoE in IBD patients and inversely an up to sixfold increased risk of IBD among EoE patients [ 128 ].…”
Section: Differential Diagnosis Of Esophageal Eosinophiliamentioning
confidence: 99%